New inequalities of Grüss--Lupaş type and Applications for Selfadjoint Operators - Alomari, Mohammad (Armenian Journal of Mathematics, 2016)
In this paper, some Čebyšev--Lupaş type inequalities are proved. New inequalities of Grüss type for Riemann--Stieltjes integral are also obtained. Applications for functions of selfadjoint operators on complex Hilbert spaces are provided as well.